Interactions Between Lr67 or Lr34 and Other Leaf Rust Resistance Genes in Wheat (Triticum aestivum) - McCallum, Brent D.; Hiebert, Colin W. (Frontiers in Plant Science, 2022)
The wheat multi-pest resistance genes Lr67 and Lr34 are similar in that they both condition resistance to many diseases, in a non-race-specific manner, and code for cellular transporters. Lr34 plays a critical role in breeding wheat for disease resistance in large part because it interacts with other resistance genes to result in effective and durable resistance. To determine if Lr67 interacts with other resistance genes in a similar manner as Lr34 six different doubled haploid populations were developed which segregated for either Lr67 or Lr34 along with a second resistance gene, either Lr13, Lr16, or Lr32. The presence or absence of each of these genes in the progeny lines was determined by molecular marker analysis. These six populations were tested for leaf rust field resistance in the same environments to compare the effects of Lr34 and Lr67 alone, and in combination with Lr13, Lr16 or Lr32. Lr67 and Lr34 significantly reduced the levels of rust severity, Lr34 showed a significant interaction with Lr13 but Lr67 did not. Both genes interacted with Lr16, and Lr67 had a significant interaction with Lr32. This analysis demonstrates the similar effect of Lr67, as seen with Lr34, on the interaction with other resistance genes to give a better level of resistance than with single resistance genes. While Lr67 is not widely deployed in agriculture, it could play an important role in disease resistance in future wheat cultivars.